2007
DOI: 10.1021/ja068067v
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Control of Transmembrane Cl- Transport

Abstract: Due to their biological importance, the complexation, sensing, and transport of anions are attracting increasing attention. 1,2 A variety of receptors based on the isophthalamide skeleton (e.g., 1 in Figure 1) have been studied, as these systems are easy to make and are effective anion receptors in organic solution. 3,4 Two strategies to improve the affinity and selectivity of anion receptors are to increase the acidity of hydrogen bond donors and/or to build more rigid scaffolds. The first strategy may, in so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 139 publications
(89 citation statements)
references
References 15 publications
1
86
0
Order By: Relevance
“…So far, there have only been two other reports concerning switching-off anion transport by deprotonation, but these involve deprotonation of phenolic OH groups which have high p K a values and the switch consequently occurs at pHs that are not physiologically relevant (pH > 7.4). 65,66 On the other hand, the ON–OFF switch in the region pH 6–7 gives the thiosquaramide based receptors more potential in the biological arena and an investigation of the biological activity of thiosquaramides is currently ongoing in our laboratories.…”
Section: Resultsmentioning
confidence: 99%
“…So far, there have only been two other reports concerning switching-off anion transport by deprotonation, but these involve deprotonation of phenolic OH groups which have high p K a values and the switch consequently occurs at pHs that are not physiologically relevant (pH > 7.4). 65,66 On the other hand, the ON–OFF switch in the region pH 6–7 gives the thiosquaramide based receptors more potential in the biological arena and an investigation of the biological activity of thiosquaramides is currently ongoing in our laboratories.…”
Section: Resultsmentioning
confidence: 99%
“…This efflux is produced via an exchange mechanism with external nitrate anions, in agreement with previous studies. 16,29 Replacing nitrate by the more hydrophilic sulfate in the external medium resulted in no anion transport activity as an anion exchange mechanism is not possible due to the higher hydrophilicity of the dianionic sulfate. A subsequent assay in which a second anion (bicarbonate) was added to the external sulfate medium showed that chloride transport by compounds 1-4 was restored, clear evidence that these compounds facilitate HCO 3 -/Cl -exchange across phospholipid membranes.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported the transmembrane chloride transport activity of 4,6-dihydroxyisophthalamide 1. 16 Isophthalamides have amide NH groups that are able to form hydrogen bonds with anions. 17 In the case of 1, conformational control of the anion binding cleft by means of intramolecular hydrogen bonds between the 4,6 dihydroxy units and the neighbouring amide carbonyls resulted in an improved anion affinity in solution and in optimal activity for transmembrane transport of chloride anion.…”
mentioning
confidence: 99%
“…Smith [75] and with J.T. Davis and R. Quesada [76] was aimed to reveal the delicate balance between ionophore conformation and its anion transport rate. In compound 14 (Fig.…”
Section: Artificial Anion Carriersmentioning
confidence: 99%